Diagnostic value of lead aVR in electrocardiography for identifying acute coronary lesions in patients with out-of-hospital cardiac arrest. (September 2019) - Yamamoto, Masaya; Witsch, Thilo; Kubota, Shuji; Hara, Hisao; Hiroi, Yukio
Abstract: Aim: There is no simple clinical tool that reliably indicates the presence of acute coronary lesions in out-of-hospital cardiac arrest (OHCA) patients without typical ST-segment elevations. ST-segment elevation in electrocardiographic lead aVR suggests global subendocardial ischemia. This study aimed to evaluate the diagnostic value of lead aVR for identifying acute coronary lesions following resuscitation from OHCA. Methods: A total of 74 patients without evidence of ST-segment elevations, who were resuscitated from OHCA, were examined. The degree of ST-segment elevation in lead aVR was measured directly after return of spontaneous circulation (ROSC) and at early follow-up. Coronary angiograms were retrospectively reviewed. Results: Acute coronary lesions were detected in 20 patients (27%). No difference in ST-segment elevation in lead aVR directly after ROSC was observed between patients with or without acute coronary lesions. However, ST-segment elevation values significantly decreased at early follow-up (median, 137 min) in patients without acute coronary lesions. An ST-segment elevation ≥0.5 mm in lead aVR at early follow-up was associated with a higher prevalence of multivessel coronary artery disease and was an independent indicator of the presence of acute coronary lesions (odds ratio, 4.41; 95% confidence interval, 1.12–17.4; p = 0.034). Conclusion: ST-segment elevation in lead aVR at early follow-up was associated with the presence of acute lesions accompanied by severe coronary artery disease in post-cardiac arrest patients without other ST-segment elevations. The analysis of ST-segment elevation in lead aVR may aid in the identification of patients who will benefit from further invasive coronary diagnostic procedures.